Immunotherapy with Native Molecule rather than Hypoallergenic Variant of Pru p 3, the Major Peach Allergen, Shows Beneficial Effects in Mice. (13th June 2018) - Rodriguez, Maria J.; Wangorsch, Andrea; Gomez, Francisca; Schülke, Stefan; Torres, Maria J.; Vieths, Stefan; Scheurer, Stephan; Toda, Masako; Mayorga, Cristobalina
Abstract : Background . The use of hypoallergenic derivatives is considered beneficial to promote the safety and efficacy of allergen-specific immunotherapy. We aimed to assess the efficacy of reduced and alkylated (R/A) Pru p 3, a hypoallergenic folding variant of the major peach allergen, in subcutaneous immunotherapy (SCIT) using a murine model of peach allergy. Methods and Results . After sensitization with Pru p 3, BALB/c mice received SCIT with Pru p 3 or R/A Pru p 3 and were challenged with Pru p 3. SCIT with Pru p 3, but not with R/A Pru p 3, suppressed anaphylaxis upon the challenge significantly. SCIT with Pru p 3 did not suppress Pru p 3-specific IgE and IgG1 production, but enhanced IgG2a production. In contrast, SCIT with R/A Pru p 3 suppressed IgE and IgG1 production, but enhanced IgG2a production only moderately. The therapeutic efficacy of SCIT with Pru p 3 was associated with induction of IL-10 and IFN- γ . Conclusion . Hypoallergenic folding variant of Pru p 3 is not likely an efficacious therapeutic component in SCIT of peach allergy. The lower efficacy of R/A Pru p 3 might be attributed to poor antigenicity and/or weak stability due to its unfolded conformation.